Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To determine the focal width of the parabola given by the equation [tex]\( y = (x+2)^2 - 3 \)[/tex], let's analyze its form and properties step-by-step.
1. Rewrite the given equation in the standard form of a parabola:
The standard form of a parabola with a vertical axis of symmetry is given by:
[tex]\[ y = a(x - h)^2 + k \][/tex]
In our given equation [tex]\( y = (x+2)^2 - 3 \)[/tex]:
[tex]\[ y = (x - (-2))^2 - 3 \][/tex]
By comparison, we identify:
[tex]\[ h = -2 \][/tex]
[tex]\[ k = -3 \][/tex]
2. Identify the vertex and the direction of the parabola:
From the equation, the vertex of the parabola is at [tex]\( (h, k) = (-2, -3) \)[/tex]. Since the squared term is [tex]\((x + 2)^2\)[/tex], which is always non-negative, and since the leading coefficient (the coefficient of the [tex]\( (x - h)^2 \)[/tex] term) is positive, the parabola opens upwards.
3. Determine the coefficient [tex]\( a \)[/tex]:
The given equation is already in the form [tex]\( y = 1(x + 2)^2 - 3 \)[/tex]:
[tex]\[ a = 1 \][/tex]
4. Relate the coefficient [tex]\( a \)[/tex] to the focal distance [tex]\( p \)[/tex]:
For a parabola in the form [tex]\( y = a(x - h)^2 + k \)[/tex], the coefficient [tex]\( a \)[/tex] is related to the focal distance [tex]\( p \)[/tex] by the formula:
[tex]\[ a = \frac{1}{4p} \][/tex]
Substituting [tex]\( a = 1 \)[/tex]:
[tex]\[ 1 = \frac{1}{4p} \][/tex]
Solving for [tex]\( p \)[/tex]:
[tex]\[ 4p = 1 \][/tex]
[tex]\[ p = \frac{1}{4} \][/tex]
5. Calculate the focal width:
The focal width of a parabola is given by [tex]\( 4p \)[/tex]. Substituting our value of [tex]\( p \)[/tex]:
[tex]\[ \text{Focal width} = 4p = 4 \times \frac{1}{4} = 1 \][/tex]
Therefore, the length of the focal width of the parabola is 1 unit.
1. Rewrite the given equation in the standard form of a parabola:
The standard form of a parabola with a vertical axis of symmetry is given by:
[tex]\[ y = a(x - h)^2 + k \][/tex]
In our given equation [tex]\( y = (x+2)^2 - 3 \)[/tex]:
[tex]\[ y = (x - (-2))^2 - 3 \][/tex]
By comparison, we identify:
[tex]\[ h = -2 \][/tex]
[tex]\[ k = -3 \][/tex]
2. Identify the vertex and the direction of the parabola:
From the equation, the vertex of the parabola is at [tex]\( (h, k) = (-2, -3) \)[/tex]. Since the squared term is [tex]\((x + 2)^2\)[/tex], which is always non-negative, and since the leading coefficient (the coefficient of the [tex]\( (x - h)^2 \)[/tex] term) is positive, the parabola opens upwards.
3. Determine the coefficient [tex]\( a \)[/tex]:
The given equation is already in the form [tex]\( y = 1(x + 2)^2 - 3 \)[/tex]:
[tex]\[ a = 1 \][/tex]
4. Relate the coefficient [tex]\( a \)[/tex] to the focal distance [tex]\( p \)[/tex]:
For a parabola in the form [tex]\( y = a(x - h)^2 + k \)[/tex], the coefficient [tex]\( a \)[/tex] is related to the focal distance [tex]\( p \)[/tex] by the formula:
[tex]\[ a = \frac{1}{4p} \][/tex]
Substituting [tex]\( a = 1 \)[/tex]:
[tex]\[ 1 = \frac{1}{4p} \][/tex]
Solving for [tex]\( p \)[/tex]:
[tex]\[ 4p = 1 \][/tex]
[tex]\[ p = \frac{1}{4} \][/tex]
5. Calculate the focal width:
The focal width of a parabola is given by [tex]\( 4p \)[/tex]. Substituting our value of [tex]\( p \)[/tex]:
[tex]\[ \text{Focal width} = 4p = 4 \times \frac{1}{4} = 1 \][/tex]
Therefore, the length of the focal width of the parabola is 1 unit.
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.